A COMPARISON BETWEEN LAPAROSCOPIC AND OPEN INGUINAL HERNIA SURGERY IN THONG NHAT HOSPITAL - Thế Anh, Phạm; Hữu Đức, Hồ; Thanh Phong, Nguyễn (Journal of Health and Aging, 2025)
To survey the characteristics of inguinal hernia and compare between the open and laparoscopic inguinal hernia surgery at Thong Nhat Hospital from April 2023 to April 2024. A restrospective study of 139 patients with laparoscopic and open inguinal hernia surgery in Thong Nhat hospital during the study period. Of 139 included patients, 97.8% were men, and the median (IQR) age was 60 (20-88) years. Compared between open and laparoscopic repair was associated with a nonsignificant duration of hospitalization. Most of patient lived in Ho Chi Minh City. We performed 72.66% open surgery. The majority of patients with unilateral inguinal hernias were treated with open surgery (80.34%) and bilateral inguinal hernias were treated with laparoscopic surgery (68.18%). The average duration of hospitalization for patients undergoing inguinal hernia surgery was 7.99±3.6 days. Most of patients has lived in Ho Chi Minh city. Duration of hospitalization was similar for the laparoscopic and open general anesthesia groups. Individualisation treatment with laparoscopic or open repair for patients and the decision should be made considering both patient and surgeon factors.
Keywords: Inguinal hernia; Open surgery; Laparoscopic; Thong Nhat Hospital